The influence of household fluidity on the health and well-being of the child - Fleetwood, Stella Angela (My University, 2013)
Research indicates that there is a strong association between household composition and household stability, and child well-being. Black South African family life has historically been affected by the social, political and economic pressures of colonialism, the migrant labour system, and Apartheid policies. It has been shown that Black households have been in a constant state of flux as members move between rural and urban households, as well as, within urban environments. This situation of intense household fluidity and household compositional changes continues to persist. High rates of urbanisation, the fluid job market, and fast social change are all associated with high levels of mobility and household compositional change. Kin networks remain a significant informal safety net for households in order to absorb change. The movement of children between family members, or child fostering is an important mechanism for maintaining networks of support. Children are frequently moved between different households in urban areas so as to maximise their care and education. These changes could potentially influence their overall well-being and, in particular, their academic performance.
Submitted in fulfilment of the requirements for the degree of MASTER OF SCIENCE Faculty of Health Sciences, University of the Witwatersrand Johannesburg, 2012
Keywords: household fluidity; household structure; family structure; Johannesburg-Soweto; birth to twenty; adolescent; grade repeats; Residential mobility; Child Development